Association of Educational Attainment With Adiposity, Type 2 Diabetes, and Coronary Artery Diseases: A Mendelian Randomization Study - Cao, Min; Cui, Bin (Frontiers in Public Health, 2020)
Background: Observational studies showed that educational attainment (EA) is associated with cardiometabolic diseases, but the long interval between exposure and outcome makes it difficult to infer causality. We herein used Mendelian randomization (MR) to examine the causal effects of EA on adiposity, type 2 diabetes (T2D) and coronary artery disease (CAD). Methods: A two-sample MR analysis was conducted using genome-wide association study (GWAS) summary statistics. 74 instrumental variables (IVs) were used to determine the causal effect of EA on the cardiometabolic diseases. Sensitivity analyses were also performed to detect the pleiotropy of the IVs. Results: Using the MR approach we found that each additional year in EA is associated with 15% lower risk of adiposity (OR 0.85 [95% CI 0.79, 0.91], P = 8.85 × 10-7), 39% lower risk in T2D (OR 0.61 [95% CI 0.50, 0.75], P = 1.16 × 10-6), and 36% decreased risk in CAD (OR 0.64 [95% CI 0.55, 0.75], P = 2.38 × 10-8) at the Bonferroni-adjusted level of significance. Conclusion: Our findings suggest a causal role of EA on the cardiometabolic diseases including adiposity, T2D and CAD.